Upper extremity distal dual bypass enables arteriovenous fistula construction in a critical limb ischemia - Nakamura, Tsukasa (J Surg Case Rep, 2019)
BACKGROUND: Arteriovenous fistula (AVF) trouble in a dialysis patient sometimes results in severe forearm ischemia. CASE PRESENTATION: We present the case of 27-year-old man with severe steal syndrome complained of AVF malfunction. There was a condition where an upstream artery of AVF is occluded and AVF is maintained by regurgitation from the palmar arch with ischemic digits. The patient underwent distal dual bypass: proximal to peripheral artery arterioarterial and arteriovenous bypasses and brachial arterioplasty. His skin perfusion pressure improved from 17 to 90 mmHg with enough quantity of blood: 250 ml/min for hemodialysis. CONCLUSIONS: In severe steal syndrome cases, it is often observed that proximal artery is occluded and AVF inflow was supplied from palmar circulation and collateral vessels. Distal dual bypass is effective to re-establish digital circulation and repair AVF malfunction simultaneously in PAD patients.